Functional auxiliary agent for artificial board production and synthesis method of functional auxiliary agent
By using functional additives containing aldehyde-reducing agents and waterproofing agents in the production of artificial boards, the formaldehyde release problem of adhesives is solved, the glue strength and environmental safety of artificial boards are improved, and the formaldehyde release amount and glue performance are achieved. promote.
Patent Information
- Application Number
- CN202411030537.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2024-12-20
AI Technical Summary
Existing artificial board adhesives release formaldehyde during the manufacturing process, contaminating the indoor environment and affecting human health. Improving synthetic formula processes to reduce formaldehyde release usually leads to a decrease in strength of artificial boards and an extended curing time.
A functional additive for artificial board production, including soft plastic ball clay, rice husk powder, adipic acid dihydrazide, alkylkone dimer emulsion, cellulose and ammonium sulfate, through aldehyde reducing agent and The synergistic effect of waterproofing agents reduces formaldehyde emission and increases the strength of the glue.
While improving the water-resistant glue strength of artificial boards, the additive significantly reduces the formaldehyde emission, and is simple in process and easy to implement. It has good adhesion, suspension and adsorption, which improves the environmental and economic benefits of artificial boards.
Smart Images

Figure CN119161824A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to a functional auxiliary agent for producing artificial boards and a synthesis method thereof. Background Art
[0002] With the reduction of forest resources and the shortage of wood, artificial boards have become an important material for furniture manufacturing and interior decoration. The adhesives used to prepare various artificial boards mainly include phenolic resin adhesives and amino resin adhesives. The artificial boards made of these adhesives will continuously release formaldehyde, polluting the indoor living environment and affecting human health. Formaldehyde is a highly toxic substance. Long-term exposure can cause a variety of diseases such as decreased immunity, abnormal smell and liver and lung function, easy hair loss, colds, general weakness, headaches, etc. In severe cases, it can also cause cell gene mutations and even cancer. Therefore, it is extremely urgent to control formaldehyde pollution in artificial boards.
[0003] The current method of removing formaldehyde released by adhesives is mainly to reduce the free formaldehyde content by improving the synthetic formula process of the adhesive, such as reducing the formaldehyde feed, controlling the pH value in the condensation reaction stage, steam dehydration or water dehydration, etc. However, such methods will lead to a decrease in the strength of the artificial board and a prolonged curing time. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a functional additive for producing artificial boards and a synthesis method thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention:
[0007] A functional additive for producing artificial boards, comprising the following raw materials in parts by weight:
[0008] 35-45 parts of soft plastic ball clay, 40-60 parts of rice husk powder, 1-5 parts of adipic acid dihydrazide, 1-10 parts of alkyl ketene dimer emulsion, 1-5 parts of cellulose, 1-5 parts of ammonium sulfate and 1-5 parts of rosin powder.
[0009] Preferably, the concentration of the alkyl ketene dimer emulsion is 20 wt %.
[0010] In the functional auxiliary agent for producing artificial boards of the present invention, the formaldehyde emission of artificial boards is reduced and the bonding strength is improved through the synergistic effect of the formaldehyde reducing agent adipic acid dihydrazide and the waterproofing agent alkyl ketene dimer emulsion (20wt%).
[0011] Preferably, the functional additive for producing artificial boards comprises the following raw materials in parts by weight:
[0012] 35-40 parts of soft plastic ball clay, 40-50 parts of rice husk powder, 3-5 parts of adipic acid dihydrazide, 1-5 parts of alkyl ketene dimer emulsion (20wt%), 1-3 parts of cellulose, 1-2 parts of ammonium sulfate and 3-5 parts of rosin powder.
[0013] More preferably, the functional additive for producing artificial boards comprises the following raw materials in parts by weight:
[0014] 35 parts of soft plastic ball clay, 45 parts of rice husk powder, 5 parts of adipic acid dihydrazide, 5 parts of alkyl ketene dimer emulsion (20wt%), 3 parts of cellulose, 2 parts of ammonium sulfate and 5 parts of rosin powder.
[0015] In the functional additive for artificial board production of the present invention, soft plastic ball clay is used as a base material, rice husk powder is used as an extender, adipic acid dihydrazide is used as a formaldehyde reducing agent, alkyl ketene dimer emulsion (20wt%) is used as a waterproofing agent, cellulose is used as a moisturizing agent, ammonium sulfate is used as a curing agent, and rosin powder is used as a tackifier. The functional additive for artificial board production synthesized by the present invention is composed of organic and inorganic materials, is a new type of material, has the characteristics of good adsorption and viscosity, and has good adhesion, suspension, waterproofness and adsorption after being mixed with resin glue. The artificial board produced by using the additive of the present invention can reduce the formaldehyde emission while improving the water-resistant bonding strength.
[0016] Preferably, the particle size of the soft plastic ball clay is 80-200 meshes. If the mesh is less than 80 meshes, it will be difficult to disperse evenly, produce slag, and affect the bonding strength. If the mesh is greater than 200 meshes, a large amount of dust will be generated, which is not conducive to environmental protection and the health of operators. The particle size of the rice husk powder is 80-200 meshes. If the mesh is less than 80 meshes, it will be difficult to disperse evenly, produce slag, and affect the bonding strength. If the mesh is greater than 200 meshes, a large amount of dust will be generated, which is not conducive to environmental protection and the health of operators. The cellulose is selected from carboxymethyl cellulose with a viscosity of 300 cP. The cellulose at this viscosity is conducive to the stability of the viscosity after the additive is mixed with the resin glue.
[0017] The second technical solution of the present invention:
[0018] The present invention also provides a method for preparing the functional additive for producing artificial boards, comprising the following steps: mixing soft plastic ball clay, rice husk powder, adipic acid dihydrazide, alkyl ketene dimer emulsion (20wt%), cellulose, ammonium sulfate and rosin powder in proportion and stirring evenly.
[0019] Preferably, the preparation method of the functional additive for artificial board production comprises the following steps: soft plastic ball clay, rice husk powder, adipic acid dihydrazide, alkyl ketene dimer emulsion (20wt%), cellulose, ammonium sulfate and rosin powder are put into a mixer in proportion, stirred and mixed for 30 minutes, and then packaged.
[0020] More preferably, before the soft plastic ball clay, rice husk powder, adipic acid dihydrazide, alkyl ketene dimer emulsion (20wt%), cellulose, ammonium sulfate and rosin powder are put into the mixer in proportion, the rice husk powder and the alkyl ketene dimer emulsion (20wt%) are fully mixed for 20 minutes and then the other components are added in sequence, and stirring is continued for 30 minutes.
[0021] The third technical solution of the present invention:
[0022] The present invention also provides a mixed artificial board adhesive, the raw materials of which contain the functional auxiliary agent for producing artificial boards and amino resin adhesive.
[0023] The fourth technical solution of the present invention:
[0024] The present invention also provides a method for preparing the above-mentioned mixed artificial board adhesive, comprising the following steps:
[0025] The functional auxiliary agent for producing artificial boards and the amino resin adhesive are evenly mixed to obtain the mixed artificial board adhesive.
[0026] Preferably, the weight ratio of the functional additive for producing artificial panels to the amino resin adhesive is 1:4.
[0027] Preferably, the amino resin adhesive is a urea-formaldehyde resin adhesive.
[0028] Compared with the prior art, the present invention has the following advantages and technical effects:
[0029] The functional additive for producing artificial boards synthesized by the present invention is composed of a variety of organic and inorganic materials and is a new type of material with the characteristics of good adsorption and viscosity. After being mixed with resin glue, it has good adhesion, suspension, waterproofness and adsorption. The artificial boards produced by using the additive of the present invention can improve the water-resistant bonding strength and reduce the formaldehyde emission.
[0030] The invention has the characteristics of unique conception, standardized process, simple operation, easy equipment, easy implementation, low price, etc. It can reduce formaldehyde emission when used in the production of artificial boards, and will produce huge ecological environmental benefits and social and economic benefits after popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0032] Figure 1This is a scanning electron microscope (SEM) image (10 μm) of the cross-section of the hybrid artificial board adhesive prepared in Example 1 after curing;
[0033] Figure 2 The wood breaking diagram of the bonding strength test of the plywood pressed by adding the mixed artificial board adhesive of Example 1;
[0034] Figure 3 This is a wood chip diagram of the bonding strength test of the plywood pressed by adding the mixed artificial board adhesive of Comparative Example 1. DETAILED DESCRIPTION
[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0040] All raw materials used in the embodiments of the present invention are purchased from the market. For example, soft plastic ball clay is purchased from Jilin Baoren Mining Co., Ltd., rice husk powder is purchased from Jilin Dafurenjia Rice Industry Co., Ltd., adipic acid dihydrazide is purchased from Wuhan Kanos Technology Co., Ltd. (CAS No.: 1071-93-8), alkyl ketene dimer emulsion (20wt%) is purchased from McLean (CAS No.: 57-11-4), cellulose is purchased from Wenan Shengli Cellulose Factory (CAS No.: 9004-32-4), ammonium sulfate is purchased from McLean (CAS No.: 7783-20-2), rosin powder is purchased from Jilin New Oriental Chemical Station; urea-formaldehyde resin adhesive is purchased from Xuzhou Yuanfeng New Material Technology Co., Ltd., with a solid content of 52%, free formaldehyde of 0.1%, and a viscosity of 80 centipoise (cP).
[0041] In the present invention, the formaldehyde emission and bonding strength testing method is as follows: 14 grams of mixed artificial board adhesive is coated on both sides of a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 centimeters, and then the two sides of the veneer coated with the mixed artificial board adhesive are respectively bonded with a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 centimeters in the vertical direction of the texture, and a hot press is used to hot press for 5 minutes at a hot pressing temperature of 115°C and a pressure of 1.0 MPa to obtain a plywood to be tested, and the formaldehyde emission and bonding strength are tested according to the method specified in GB / T 17657-2022.
[0042] The wood damage rate specified in GBT 33333-2016 is defined as: when the bonded specimen is damaged, the percentage of the wood damage area on the bonding surface to the bonding area. In the present invention, the wood damage rate reflects the degree of damage of the specimen during the test.
[0043] The technical solution of the present invention is further illustrated by the following embodiments.
[0044] Example 1
[0045] Weigh 35 kg of soft plastic ball clay (particle size of 100 mesh), 45 kg of rice husk powder (particle size of 100 mesh), 5 kg of adipic acid dihydrazide, 5 kg of alkyl ketene dimer emulsion (20%, mass fraction, the same below), 3 kg of cellulose, 2 kg of ammonium sulfate, and 5 kg of rosin powder, put all the raw materials into a blender, stir and mix for 30 minutes, and package to obtain a finished functional additive for wood-based panel production.
[0046] 25g of the functional additive for producing artificial boards was mixed evenly with 100g of urea-formaldehyde resin adhesive to obtain a mixed artificial board adhesive. The SEM image of the fracture after curing is shown in FIG. Figure 1It can be seen that the fracture surface of the mixed artificial board adhesive synthesized by adding the additive of this embodiment becomes rough after curing, and more short silver streaks appear. These silver streaks can absorb impact energy, disperse stress, and improve the toughness of the resin, thereby improving the impact resistance of the matrix, which is reflected in the improvement of the bonding strength of the prepared artificial board. The curing time of the mixed artificial board adhesive of this embodiment is 66 seconds. The shear strength test of the glue layer of the plywood pressed by adding the mixed artificial board adhesive of this embodiment is shown in the figure. Figure 2 (Test standard refers to GB / T 17657-2022), by Figure 2 It can be seen that the wood breakage rate is 90-100% (the wood breakage rate here is the average value of multiple test pieces to avoid contingency, the same below).
[0047] 14 grams of the above-mentioned mixed artificial board adhesive is coated on each side of a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm, and then the two sides of the veneer coated with the mixed artificial board adhesive are respectively bonded with a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm in the direction perpendicular to the texture of each side, and hot pressed for 5 minutes using a hot press at a hot pressing temperature of 115°C and a pressure of 1.0 MPa to obtain the plywood to be tested.
[0048] The bonding strength of the plywood produced using the mixed artificial board adhesive of this embodiment was measured according to the method specified in GB / T 17657-2022 to be 1.35 MPa, the formaldehyde emission was 0.66 mg / L 7 days after the artificial board was prepared, and the formaldehyde emission was 0.58 mg / L 30 days after the preparation.
[0049] Example 2
[0050] Weigh 35 kg of soft plastic ball clay (particle size of 100 mesh), 45 kg of rice husk powder (particle size of 100 mesh), 4 kg of adipic acid dihydrazide, 6 kg of alkyl ketene dimer emulsion (20%), 3 kg of cellulose, 2 kg of ammonium sulfate, and 5 kg of rosin powder, put all the above raw materials into a blender, stir and mix for 30 minutes, and package to obtain a functional additive product for wood-based panel production.
[0051] 25 g of the functional additive for producing artificial boards was uniformly mixed with 100 g of urea-formaldehyde resin adhesive to obtain a mixed artificial board adhesive, and the curing time was 62 seconds.
[0052] 14 grams of the above-mentioned mixed artificial board adhesive is coated on each side of a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm, and then the two sides of the veneer coated with the mixed artificial board adhesive are respectively bonded with a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm in the direction perpendicular to the texture of each side, and hot pressed for 5 minutes using a hot press at a hot pressing temperature of 115°C and a pressure of 1.0 MPa to obtain the plywood to be tested.
[0053] The bonding strength of the plywood produced using the mixed artificial board adhesive of this embodiment was measured according to the method specified in GB / T 17657-2022 to be 1.39 MPa, and the formaldehyde emission was 0.68 mg / L 7 days after the preparation of the artificial board, and the formaldehyde emission was 0.61 mg / L 30 days after the preparation of the artificial board.
[0054] Example 3
[0055] Weigh 35 kg of soft plastic ball clay (particle size of 100 mesh), 45 kg of rice husk powder (particle size of 100 mesh), 3 kg of adipic acid dihydrazide, 7 kg of alkyl ketene dimer emulsion (20%), 3 kg of cellulose, 2 kg of ammonium sulfate, and 5 kg of rosin powder, put all the above raw materials into a blender, stir and mix for 30 minutes, and package to obtain a functional additive product for wood-based panel production.
[0056] 25 g of the functional additive for producing artificial boards was uniformly mixed with 100 g of urea-formaldehyde resin adhesive to obtain a mixed artificial board adhesive, and the curing time was 60 seconds.
[0057] 14 grams of the above-mentioned mixed artificial board adhesive is coated on each side of a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm, and then the two sides of the veneer coated with the mixed artificial board adhesive are respectively bonded with a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm in the direction perpendicular to the texture of each side, and hot pressed for 5 minutes using a hot press at a hot pressing temperature of 115°C and a pressure of 1.0 MPa to obtain the plywood to be tested.
[0058] The bonding strength of the plywood produced using the mixed artificial board adhesive of this embodiment was measured according to the method specified in GB / T 17657-2022 to be 1.41 MPa, the formaldehyde emission after 7 days was 0.72 mg / L, and the formaldehyde emission after 30 days was 0.64 mg / L after the artificial board was prepared.
[0059] Example 4
[0060] Weigh 35 kg of soft plastic ball clay (particle size of 100 mesh), 45 kg of rice husk powder (particle size of 100 mesh), 2 kg of adipic acid dihydrazide, 8 kg of alkyl ketene dimer emulsion (20%), 3 kg of cellulose, 2 kg of ammonium sulfate, and 5 kg of rosin powder, put all the above raw materials into a blender, stir and mix for 30 minutes, and package to obtain a functional additive product for wood-based panel production.
[0061] 25 g of the functional additive for producing artificial boards was uniformly mixed with 100 g of urea-formaldehyde resin adhesive to obtain a mixed artificial board adhesive, and the curing time was 60 seconds.
[0062] 14 grams of the above-mentioned mixed artificial board adhesive is coated on each side of a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm, and then the two sides of the veneer coated with the mixed artificial board adhesive are respectively bonded with a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm in the direction perpendicular to the texture of each side, and hot pressed for 5 minutes using a hot press at a hot pressing temperature of 115°C and a pressure of 1.0 MPa to obtain the plywood to be tested.
[0063] The bonding strength of the plywood produced using the mixed artificial board adhesive of this embodiment was measured according to the method specified in GB / T 17657-2022 to be 1.49 MPa, the formaldehyde emission after 7 days was 0.77 mg / L, and the formaldehyde emission after 30 days was 0.69 mg / L after the artificial board was prepared.
[0064] Example 5
[0065] Weigh 35 kg of soft plastic ball clay (particle size of 100 mesh), 45 kg of rice husk powder (particle size of 100 mesh), 1 kg of adipic acid dihydrazide, 6 kg of alkyl ketene dimer emulsion (20%), 1 kg of cellulose, 2 kg of ammonium sulfate, and 1 kg of rosin powder, put all the above raw materials into a blender, stir and mix for 30 minutes, and package to obtain a functional additive product for wood-based panel production.
[0066] 25 g of the functional additive for artificial board production was uniformly mixed with 100 g of urea-formaldehyde resin adhesive to obtain a mixed artificial board adhesive, and the curing time was 59 seconds.
[0067] 14 grams of the above-mentioned mixed artificial board adhesive is coated on each side of a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm, and then the two sides of the veneer coated with the mixed artificial board adhesive are respectively bonded with a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm in the direction perpendicular to the texture of each side, and hot pressed for 5 minutes using a hot press at a hot pressing temperature of 115°C and a pressure of 1.0 MPa to obtain the plywood to be tested.
[0068] The bonding strength of the plywood produced using the mixed artificial board adhesive of this embodiment was measured according to the method specified in GB / T 17657-2022 to be 1.52 MPa, the formaldehyde emission after 7 days of preparation of the artificial board was 0.81 mg / L, and the formaldehyde emission after 30 days was 0.70 mg / L.
[0069] Example 6
[0070] Same as Example 1, except that the soft plastic ball clay, rice husk powder, adipic acid dihydrazide, alkyl ketene dimer emulsion (20%), cellulose, ammonium sulfate and rosin powder are put into the mixer in proportion, and the rice husk powder and alkyl ketene dimer emulsion (20%) are fully mixed for 20 minutes before adding other components in sequence and stirring for 30 minutes. The preparation method of the plywood to be tested is the same as that of Example 1. According to the method specified in GB / T 17657-2022, the bonding strength of the plywood produced by the mixed artificial board adhesive of this embodiment is measured to be 1.38MPa, and the formaldehyde emission after 7 days after the preparation of the artificial board is 0.63mg / L, and the formaldehyde emission after 30 days is 0.55mg / L.
[0071] Example 7
[0072] Weigh 45 kg of soft plastic ball clay (particle size of 100 mesh), 40 kg of rice husk powder (particle size of 100 mesh), 3 kg of adipic acid dihydrazide, 1 kg of alkyl ketene dimer emulsion (20%), 5 kg of cellulose, 5 kg of ammonium sulfate, and 3 kg of rosin powder, put all the above raw materials into a blender, stir and mix for 30 minutes, and package to obtain a functional additive product for wood-based panel production.
[0073] 25 g of the functional additive for producing artificial boards was uniformly mixed with 100 g of urea-formaldehyde resin adhesive to obtain a mixed artificial board adhesive, and the curing time was 57 seconds.
[0074] The preparation method of the plywood to be tested is the same as that in Example 1. The bonding strength of the plywood produced by the mixed artificial board adhesive of this embodiment is measured according to the method specified in GB / T 17657-2022 to be 1.62 MPa, and the formaldehyde emission after 7 days after the preparation of the artificial board is 0.7 mg / L, and the formaldehyde emission after 30 days is 0.62 mg / L.
[0075] Example 8
[0076] Weigh 35 kg of soft plastic ball clay (particle size of 100 mesh), 60 kg of rice husk powder (particle size of 100 mesh), 3 kg of adipic acid dihydrazide, 1 kg of alkyl ketene dimer emulsion (20%), 3 kg of cellulose, 2 kg of ammonium sulfate, and 5 kg of rosin powder, put all the above raw materials into a blender, stir and mix for 30 minutes, and package to obtain a functional additive product for wood-based panel production.
[0077] 25 g of the functional additive for producing artificial boards was uniformly mixed with 100 g of urea-formaldehyde resin adhesive to obtain a mixed artificial board adhesive, and the curing time was 60 seconds.
[0078] The preparation method of the plywood to be tested is the same as that in Example 1. According to the method specified in GB / T 17657-2022, the bonding strength of the plywood produced by using the mixed artificial board adhesive in this embodiment is measured to be 1.53 MPa, and the formaldehyde emission after 7 days after the preparation of the artificial board is 0.71 mg / L, and the formaldehyde emission after 30 days is 0.60 mg / L.
[0079] Comparative Example 1
[0080] 25 g of flour and 100 g of urea-formaldehyde resin adhesive were evenly mixed to obtain a mixed artificial board adhesive with a curing time of 87 seconds.
[0081] 14 grams of the above-mentioned mixed artificial board adhesive is coated on each side of a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm, and then the two sides of the veneer coated with the adhesive are respectively bonded with a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm in the direction perpendicular to the texture of the two sides of the veneer. Use a hot press to hot press for 5 minutes at a hot pressing temperature of 115°C and a pressure of 1.0 MPa to obtain the plywood to be tested.
[0082] The bonding strength of the plywood produced by using the mixed artificial board adhesive in this comparative example was measured according to the method specified in GB / T 17657-2022 to be 1.09 MPa, the formaldehyde emission after 7 days after the preparation of the artificial board was 1.40 mg / L, and the formaldehyde emission after 30 days was 1.08 mg / L.
[0083] Figure 3 The wood breakage diagram of the bonding strength test of the plywood pressed by adding the mixed artificial board adhesive of Comparative Example 1 shows that the wood breakage rate is 20-30%.
[0084] Comparative Example 2
[0085] 12.5 g of flour was mixed with 12.5 g of the functional auxiliary agent for producing synthetic artificial boards in Example 1, and then mixed evenly with 100 g of urea-formaldehyde resin adhesive to obtain a mixed artificial board adhesive, and the curing time was 75 seconds.
[0086] 14 grams of the above-mentioned mixed artificial board adhesive is coated on each side of a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm, and then the two sides of the veneer coated with the adhesive are respectively bonded with a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm in the direction perpendicular to the texture of the two sides of the veneer. Use a hot press to hot press for 5 minutes at a hot pressing temperature of 115°C and a pressure of 1.0 MPa to obtain the plywood to be tested.
[0087] The bonding strength of the plywood produced by using the mixed artificial board adhesive in this comparative example was measured according to the method specified in GB / T 17657-2022 to be 1.22 MPa, the formaldehyde emission after 7 days after the preparation of the artificial board was 0.92 mg / L, and the formaldehyde emission after 30 days was 0.73 mg / L.
[0088] Comparative Example 3
[0089] Same as Example 1, except that adipic acid dihydrazide is not added when the functional additive for producing synthetic wood-based panels is used.
[0090] Since adipic acid dihydrazide was not added to the auxiliary agent of this comparative example, the ability of the auxiliary agent to capture formaldehyde was reduced. 25 g of the auxiliary agent was evenly mixed with 100 g of urea-formaldehyde resin adhesive to obtain a mixed artificial board adhesive, and the curing time was 55 seconds.
[0091] 14 grams of the above-mentioned mixed artificial board adhesive is coated on each side of a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm, and then the two sides of the veneer coated with the adhesive are respectively bonded with a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm in the direction perpendicular to the texture of the two sides of the veneer. Use a hot press to hot press for 5 minutes at a hot pressing temperature of 115°C and a pressure of 1.0 MPa to obtain the plywood to be tested.
[0092] The bonding strength of the plywood produced by using the mixed artificial board adhesive in this comparative example was measured according to the method specified in GB / T 17657-2022 to be 1.26 MPa, the formaldehyde emission after 7 days after the preparation of the artificial board was 1.18 mg / L, and the formaldehyde emission after 30 days was 0.98 mg / L.
[0093] Comparative Example 4
[0094] Same as Example 1, except that the alkyl ketene dimer emulsion (20%) is not added when the functional additive for producing synthetic wood-based panels is used.
[0095] Since the auxiliary agent of this comparative example does not contain alkyl ketene dimer emulsion (20%), the water resistance of the auxiliary agent is reduced (water boiling time is 5h), and the bonding strength of the plywood is reduced (to 1.19MPa), which shows that the wet strength of the board is greatly reduced. 25g of the auxiliary agent is evenly mixed with 100g of urea-formaldehyde resin adhesive to obtain a mixed artificial board adhesive, and the curing time is 68 seconds.
[0096] 14 grams of the above-mentioned mixed artificial board adhesive is coated on each side of a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm, and then the two sides of the veneer coated with the adhesive are respectively bonded with a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm in the direction perpendicular to the texture of the two sides of the veneer. Use a hot press to hot press for 5 minutes at a hot pressing temperature of 115°C and a pressure of 1.0 MPa to obtain the plywood to be tested.
[0097] The bonding strength of the plywood produced by using the mixed artificial board adhesive in this comparative example was measured according to the method specified in GB / T 17657-2022 to be 1.19 MPa, the formaldehyde emission after 7 days after the preparation of the artificial board was 0.71 mg / L, and the formaldehyde emission after 30 days was 0.58 mg / L.
[0098] Comparative Example 5
[0099] Same as Example 1, except that cellulose and ammonium sulfate are not added when the functional additives for producing synthetic wood-based panels are used.
[0100] Since the auxiliary agent of this comparative example does not contain cellulose and ammonium sulfate, the auxiliary agent has low viscosity and slow curing speed. 25g of the auxiliary agent is evenly mixed with 100g of urea-formaldehyde resin adhesive to obtain a mixed artificial board adhesive, and the curing time is 85 seconds.
[0101] 14 grams of the above-mentioned mixed artificial board adhesive is coated on each side of a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm, and then the two sides of the veneer coated with the adhesive are respectively bonded with a poplar veneer with a single-sided area of 0.1 square meters and a thickness of 0.18 cm in the direction perpendicular to the texture of the two sides of the veneer. Use a hot press to hot press for 5 minutes at a hot pressing temperature of 115°C and a pressure of 1.0 MPa to obtain the plywood to be tested.
[0102] The bonding strength of the plywood produced by using the mixed artificial board adhesive in this comparative example was measured according to the method specified in GB / T 17657-2022 to be 1.21 MPa, the formaldehyde emission after 7 days after the preparation of the artificial board was 0.82 mg / L, and the formaldehyde emission after 30 days was 0.78 mg / L.
[0103] The properties of the functional additives for producing artificial boards synthesized in Examples 1 to 5 and Comparative Examples 1 to 2 are shown in Table 1. As can be seen from Table 1, the plywood produced using the additives of the present invention has a long boiling water resistance time, high bonding strength, and low formaldehyde emission, and its comprehensive performance is better than that of the plywood pressed by traditional glue blending flour.
[0104] Table 1 Performance of functional additives for artificial board production synthesized in Examples 1 to 5 and Comparative Examples 1 to 2
[0105]
[0106] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A functional additive for the production of artificial boards, It is characterized in that According to weight parts, it includes the following raw materials: 35-45 parts of soft plastic ball clay, 40-60 parts of rice husk powder, 1-5 parts of adipic acid dihydrazide, 1-10 parts of alkyl ketene dimer emulsion, 1-5 parts of cellulose, 1-5 parts of ammonium sulfate and 1-5 parts of rosin powder.
2. The functional additive for producing artificial boards according to claim 1, It is characterized in that According to weight parts, it includes the following raw materials: 35-40 parts of soft plastic ball clay, 40-50 parts of rice husk powder, 3-5 parts of adipic acid dihydrazide, 1-5 parts of alkyl ketene dimer emulsion, 1-3 parts of cellulose, 1-2 parts of ammonium sulfate and 3-5 parts of rosin powder.
3. The functional additive for producing artificial boards according to claim 2, It is characterized in that According to weight parts, it includes the following raw materials: 35 parts of soft plastic ball clay, 45 parts of rice husk powder, 5 parts of adipic acid dihydrazide, 5 parts of alkyl ketene dimer emulsion, 3 parts of cellulose, 2 parts of ammonium sulfate and 5 parts of rosin powder.
4. The functional additive for producing artificial boards according to any one of claims 1 to 3, It is characterized in that The particle size of the soft plastic ball clay is 80-200 meshes; the particle size of the rice husk powder is 80-200 meshes.
5. A method for preparing the functional additive for producing artificial boards according to any one of claims 1 to 4, It is characterized in that The following steps are involved: Mix soft plastic ball clay, rice husk powder, adipic acid dihydrazide, alkyl ketene dimer emulsion, cellulose, ammonium sulfate and rosin powder in proportion and stir evenly.
6. A mixed artificial board adhesive, It is characterized in that The raw materials contain the functional additive for producing artificial panels as claimed in any one of claims 1 to 4 and an amino resin adhesive.
7. A method for preparing the hybrid wood-based panel adhesive according to claim 6, It is characterized in that The following steps are involved: The functional auxiliary agent for producing artificial boards and the amino resin adhesive are evenly mixed to obtain the mixed artificial board adhesive.
8. The method for preparing the hybrid wood-based panel adhesive according to claim 7, It is characterized in that The weight ratio of the functional additive for producing artificial boards to the amino resin adhesive is 1:4.
